Transformation of Agrarian Land in the Urban Periphery: Dispossession, Legalization and Dispute in Cuautlancingo, Puebla - Méndez Espinoza, José Arturo (2025)
This study identifies the adverse context for the reproduction of peri-urban family farming in Cuautlancingo, Puebla, through a case study that analyzes the territorial transformations shaping its peri-urban area. The analysis shows that these transformations reflect a complex process of spatial, socioeconomic, and cultural reconfiguration, underpinned by dynamics of accumulation by dispossession (AxD). Urban expansion, neoliberal policies, and real-estate speculation have displaced traditional agricultural practices, fostering land-tenure changes and legalization mechanisms of ejido property that integrate agricultural land into the real-estate market. Among the findings, more than 40 % of agricultural areas were lost between 2005 and 2021 due to growth in the industrial and housing sectors. Nevertheless, agriculture persists as a sociocultural practice and a source of local identity. The research concludes that, without effective protection and territorial planning mechanisms, peri-urban agriculture in Cuautlancingo is at risk of disappearing under urban and industrial pressures, with implications for local food security.